Pemberdayaan masyarakat pembudidaya ikan lele di Gampong Hagu Teungoh dengan teknik pemijahan secara induksi untuk menghasilkan stok benih unggul [Empowering the catfish breaking community in Hagu Teungoh Village using inductional spawning techniques to produce superior seed stock] - Mahdaliana, Mahdaliana; Salamah, Salamah; Hartami, Prama; Rusydi, Rachmawati; Muktitama, Asih Makarti; Kamil, Ade Ikhsan (Universitas Syiah Kuala, 2024)
Hagu Teungoh Village is one of the villages located on the coast of Lhokseumawe City which has good potential in the field of fisheries. One of the business units that can support the economy of the people in this region is catfish farming. Therefore, it is necessary to empower catfish farmers so that the community knows modern spawning techniques which can later increase production which has an impact on community income. The purpose of this community empowerment program is to apply innovations to the community, especially catfish farmers in induction spawning activities, natural and artificial hatcheries, and enlargement. This community empowerment service activity is carried out by providing counseling and training related to induced catfish spawning techniques to produce superior seed stock. The approach method used is directly by providing information and practicing new innovative techniques directly. The results of the activity showed that the participants' knowledge level increased after attending counseling and training on hormonal catfish spawning techniques. 98.88% of participants knew the process of stripping catfish broodstock and caring for catfish fry, and 100% of participants knew the types of hormones and doses used for spawning. This counseling activity has a positive impact in overcoming the problems faced by catfish farmers. In conclusion, based on the survey results, the percentage of catfish farmers in Hagu Teungoh Village who know the techniques of hormonal fish spawning has increased dramatically.